Architecture as an Allusion: The Work of Herman Hiller - Lisa Diedrich; Wilbur Jobe (Oz, 2004)
It isn’t really clear who happened to start the game off. And it really makes no difference since, in the last analysis, you always need several people to play a game. What is more important is what is being played.